Angels in Late Ancient Christianity. By Ellen Muehlberger - Arthur, Rosemary A. (The journal of theological studies, 2014)
Although angels appear frequently in Scripture and are integral to Christian tradition, there was, as the relatively late (sixth-century) date of the Ps.-Dionysian corpus indicates, no single unified concept of angels in the late antique period. This was partly due to the reticence felt by many: a disinclination to speculate about angels, on the grounds that, if something was not specified in detail in Scripture, it was beyond human knowledge, and might even be dangerous to enquire into. This was the position taken by Augustine of Hippo and hence by the Western church subsequently. There was, however, no doubt about the existence of angels and of their interaction with human beings.